Leadership in Action Inklings - A Mid-Career Leadership Curriculum for High-Potential Leaders - Campbell, David P. (Center for Creative Leadership, 1997)
A high-potential program should fly the flag, teach the company, train the individual, build networks, and invoke the arts and sciences.
Title from content provider
Keywords: Leadership